Sit-tight syndrome in political renewal in Nigeria - Opeyemi, Miss Aboyade (2018)
Political instability, degrading state of the Nigerian polity and a constant need to validate the legality of its democracy is a riptide to the political renewal process. This study examines the underlying factors of sit-tight syndrome and its effects to political development in Nigeria from the onset of democratic practice in the country. The study tends to answer important questions on political decay via failures of having a viable government for years. This study employs the quantitative method in providing a framework of the problem. In the analysis section, a statistical test was performed to bring more understanding on the survey done categorically to focus on the objectives of the study. This study found three major factors that formed the basis of analysis namely: (i) god fatherism, (ii) corruption and (iii) electoral process all impactful on the political renewal in Nigeria. They act as determinant factors that can affect the political renewal system in Nigeria. Finally, the study recommends that the research should be encouraged in the academia and the Nigerian government can focus on the identified loopholes to enhance political development and safeguard the future of the nation.